2022
DOI: 10.3389/fcvm.2021.795267
|View full text |Cite
|
Sign up to set email alerts
|

Antihypertensive Medication Use and Its Effects on Blood Pressure and Haemodynamics in a Tri-ethnic Population Cohort: Southall and Brent Revisited (SABRE)

Abstract: Objectives:We characterised differences in BP control and use of antihypertensive medications in European (EA), South Asian (SA) and African-Caribbean (AC) people with hypertension and investigated the potential role of type 2 diabetes (T2DM), reduced arterial compliance (Ca), and antihypertensive medication use in any differences.Methods:Analysis was restricted to individuals with hypertension [age range 59–85 years; N = 852 (EA = 328, SA = 356, and AC =168)]. Questionnaires, anthropometry, BP measurements, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
1
3
0
Order By: Relevance
“…However, our finding of higher rates of timely antihypertensive initiation for people of South Asian or African/African Caribbean than European ethnicity is corroborated by previous UK cross-sectional studies demonstrating higher proportions of treated hypertension in the former ethnic groups. 6 , 16 Furthermore, a systematic review of studies from Europe showed similar rates of treatment for South Asian and European groups, and higher rates in African groups, partly supporting our findings. 18 Explanations are uncertain; a possibility is physician perception of heightened CVD risk in these groups, following the propagation of guidelines and risk scores emphasising this.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…However, our finding of higher rates of timely antihypertensive initiation for people of South Asian or African/African Caribbean than European ethnicity is corroborated by previous UK cross-sectional studies demonstrating higher proportions of treated hypertension in the former ethnic groups. 6 , 16 Furthermore, a systematic review of studies from Europe showed similar rates of treatment for South Asian and European groups, and higher rates in African groups, partly supporting our findings. 18 Explanations are uncertain; a possibility is physician perception of heightened CVD risk in these groups, following the propagation of guidelines and risk scores emphasising this.…”
Section: Discussionsupporting
confidence: 87%
“…As far as we are aware, no studies simultaneously compare all these factors by ethnicity, nor examine their contribution to ethnic differences in BP control. Further, UK South Asian and African/African Caribbean populations have far higher rates of diabetes than white European groups 5 and our previous work suggests ethnic differences in BP control are partly explained by diabetes, 6 but this requires substantiation in larger datasets.…”
Section: Introductionmentioning
confidence: 79%
“… Antihypertensive Drug: Antihypertensive drugs may decrease cardiac output by either inhibiting myocardial contractility or reducing ventricular filling pressure 6 .…”
Section: Medication Of Hypertensionmentioning
confidence: 99%
“…Hypertension is expected to impact up to 1 billion individuals around the world, resulting in 7.1 million deaths per year. It is estimated that 1% of high-risk patients will experience a high blood pressure at some point, and that hypertensive incidents report for 25% of all clinical visits to the clinical stage of an emergency unit (EU), with hypertensive incidents being identified in one-third of such cases 1 .…”
Section: Introductionmentioning
confidence: 99%